2009
DOI: 10.1007/s11172-009-0069-4
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties of a new group of regulatory proteins isolated from various mammal tissues

Abstract: The found similarity of the set of physicochemical characteristics of regulatory proteins active in microdoses isolated from various mammal tissues allows them to be assigned to a new group of previously unknown bioregulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…[ 40 , 41 ]. Of the peptide/protein bioregulators of this group, many of them are glycosilated derivatives and consist of peptide–protein complexes with similar physico–chemical properties exhibiting close biological activity [ 42 , 43 ]. The first studies on the use of similar bioregularors loaded in serum-albumin-derived cryogels for the induction of bone tissue regeneration have shown rather promising potential of such delivery systems [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 40 , 41 ]. Of the peptide/protein bioregulators of this group, many of them are glycosilated derivatives and consist of peptide–protein complexes with similar physico–chemical properties exhibiting close biological activity [ 42 , 43 ]. The first studies on the use of similar bioregularors loaded in serum-albumin-derived cryogels for the induction of bone tissue regeneration have shown rather promising potential of such delivery systems [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…These bioregulators are resistant to various physical and chemical factors: changes in pH, temperature, the action of chelating agents, etc. Their tendency toward intermolecular association with the formation of nanoparticles 50–300 nm in size was also noted, and the nanoscale state determines the nature of their activity [ 3 , 4 ]. The similarity of the physicochemical properties and the nature of the biological action made it possible to separate these bioregulators into a group of membranotropic homeostatic tissue-specific bioregulators (MHTB) [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…For MHTBs isolated from sclera, pigment epithelium, and cattle serum, it was found that the modulator protein is Bos taurus serum albumin of a certain isoform [ [4] , [5] , [6] ]. It should be noted that carbohydrates and lipids were detected in the peptide-protein complex, however, their functional significance in the composition of MHTB remains unknown [ 3 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It was established that animal MHTB are peptide protein complexes with extracellu lar localization. MHB activity is determined by small peptides with molecular weights of 1000-6000 Da that bind with proteins modulating their biological effects [4][5][6][7]. The distinctive properties of MHTB include activity in very low doses (VLD), tissue but not species specificity, and the ability to stimulate the recovery and repair processes in injured or pathologically changed tissues due to the additional activation of cell regenera tion sources [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…All members of this group of bioregulators exhibit similar physical and chemical properties [7]. An experimental approach involving extraction from tis sues and a range of conventional biochemical methods is used for isolation and further purification of these bioregulators from various sources.…”
Section: Introductionmentioning
confidence: 99%